Uma metodologia para desenvolver simulações distribuídas HLA usando DSEEP guiado a modelos com OPM e UML - Schittler, João Gabriel da Cunha (2024)
Distributed simulations aim to recreate some real behavior using computer networks; they are often geographically distributed as well. One widely used approach to develop distributed simulations is to use a pre-established standard for network communication between simulators; one such standard is High-Level Architecture (HLA) (IEEE, 2010). However, the development of source code for such standards is often complex and error-prone, making code generators a good option for its development. Model Driven Architectures (MDA) (OMG, 2023) have been explored to generate efficient source code based on highlevel conceptual models. Nevertheless, using MDA for code generation creates another challenge: the specification and development of accurate high-level models of the simulation, which can be quite difficult if the project stakeholders cannot properly understand the models. This work, centered in HLA project development, explores the use of ObjectProcess Methodology (DORI, 2002) in a methodology for developing distributed simulations with a conceptual modeling step that is natural, understandable to stakeholders and that guarantees automatic transformation from high-level (human-friendly) specifications into HLA source code for the specified simulation. The proposed methodology is aligned to the Distributed Simulation Engineering and Execution Process (DSEEP) and maintains the possibility of using UML as a modeling language. This work also contains a series of experiments that aim to validate the contributions, showcasing that the developed methodology can achieve its objectives and that its use is appropriate for developing distributed simulations.